A COMPARISON OF SOIL NITROGEN AVAILABILITY ALONG HILLSLOPES FOR A PREVIOUSLY MINED RECLAIMED WETLAND AND TWO NATURAL WETLANDS IN FORT MCMURRAY, ALBERTA - Thorne, Chelsea (2015)
In situ measurements of soil nitrogen dynamics is a potential method for evaluating the health of constructed wetlands following oil sands mining. The objective of this study is to measure and compare the soil nitrogen availability of a reclaimed fen (Sandhill fen) with a nutrient-rich reference fen (Poplar fen) and a nutrient-poor reference fen (Pauciflora fen) in the Athabasca oil sands region of northern Alberta. Total Nitrogen (TN), Nitrate (NO3-) and Ammonium (NH4+) supply rates were determined along wetland hillslope transects using Western Ag Innovations Plant Root Simulator (PRSTM) probes at all three sites in 2014. Net N mineralization, net nitrification and net ammonification were determined simultaneously using the buried polyethylene bag sampling method. Overall, TN supply rates were greatest at the poor fen and least at the constructed Sandhill fen. In contrast, mineralization was greatest at the rich fen but again least at the Sandhill fen. Mineralization at the Sandhill fen was controlled evenly by ammonification and nitrification, whereas the two natural sites were controlled by ammonification. Relatively low N supply rates and mineralization at the Sandhill fen were likely due to lower soil organic matter and limited soil moisture in these newly constructed substrates. Spatial differences along the hillslopes also varied among sites. The Sandhill fen had higher TN supply rates at the upslope positions but no significant differences in net N mineralization rates along the hillslopes. The rich fen also had higher TN supply rates at the upslope but greatest mineralization rates downslope. These results highlight the importance of N storage and transport processes and offer insight into the N status of a constructed fen. Thesis Master of Science (MSc)